CHOICE OF TREATMENT OPTIONS FOR CYSTIC LYMPHSTIC MALFORMATIONS IN THE HEAD AND NECK REGION: TREATMENT EXPERIENCE OF 81 CHILDREN - Benzar, I. M. (International Journal of Medicine and Medical Research, 2017)
Background. Surgery has previously been the only treatment for lymphatic malformations (LMs), but in the head and neck region is challenging due to the risk of scarring, nerve damage, recurrence. Sclerotherapy may be a perfect alternative. Objective. The aim of the study is to determine the efficacy and safety of the OK-432 sclerotherapy in the children with craniofacial LMs. Methods. 81 children with head and neck LM between December 2010 and March 2017were involved into the study. The follow-up period was from 6 to 79 months. According to the size of cysts, LMs were classified into macrocystic, microcystic, and mixed. The result of the treatment of LMs was determined by the percentage of reduction in size as excellent (decrease by more than 90%), good (by 50%-89%), satisfactory (by 20%-49%) and none (by less than 20%). Results. The macrocystic LMs diagnosed in 41.97% of patients, microcystic - in 12.35%, and mixed – in 45.68% of children. OK-432 sclerotherapy only was performed for 83.9% of patients and in 12.3% in combination with surgery. The range of sclerotherapy sessions was from 1 to 11. An excellent result in 96.97% of cases was evidenced in the patients with macrocystic LM. Poor result was proved in the patients with microcystic LMs; the most of them (55.56%) had satisfactory result. In the patients with mixed LM, an excellent and good result was evidenced in 83.33%. After 198 sessions of OK-432 sclerotherapy, complications associated with the treatment occurred in 5 (2.52%) cases. Conclusions. OK-432 sclerotherapy is a safe and effective treatment of head and neck LMs in children. Macrocystic LMs proved the best response to OK-432 treatment.